Unraveling the role of HIF and epigenetic regulation in pulmonary arterial hypertension: implications for clinical research and its therapeutic approach - Mitra, Ankita; Yi, Dan; Dai, Zhiyu; de Jesus Perez, Vinicio (Frontiers in Medicine, 2024)
Pulmonary arterial hypertension (PAH) is characterized by pulmonary vascular remodeling with high pulmonary pressure, which ultimately leads to right heart failure and premature death. Emerging evidence suggests that both hypoxia and epigenetics play a pivotal role in the pathogenesis of PAH development. In this review article, we summarize the current developments in regulation of hypoxia inducible factor (HIF) isoforms in PAH vascular remodeling and the development of suitable animal models for discovery and testing of HIF pathway-targeting PAH therapeutics. In addition, we also discuss the epigenetic regulation of HIFdependent isoforms in PAH and its therapeutic potential from a new perspective which highlights the importance of HIF isoform-specific targeting as a novel salutary strategy for PAH treatment.